The basic structure of ethical norms - Ahmed Shogar, Ibrahim Adam (IIUM Press, 2015)
THIS BOOK Taking in account the ethical implications of modern science and technology on nature and human, this book highlights the importance of ethics and moral values in human life. Knowledge and values are the two indispensible aspects of meaningful life. Aided by these two means, mankind has been able to achieve constant developments throughout the history. Along the course of history, Divine guidance has been revealed for moral perfection and total reconstruction of the worldview; thus, the modern value-free progression in science and technologies invites the attention for moral research. This book is designed to provide the essential knowledge on ethics and moral values. It is a theoretical study on the basic structure of ethical norms from both Islamic tradition and modern research perspectives. The central aim of the book is to expose readers to the general framework of ethical theories and moral norms. It especially highlights the relationship between facts and values; the major classifications of ethical norms in Qur`anic perspective; meaning of descriptive and normative ethics; the major classifications of ethical theories and virtue based ethical systems.